1998
DOI: 10.1016/s0021-9150(98)00078-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chylomicron remnants on endothelial cell function in the isolated perfused rat aorta

Abstract: . (1998). The influence of chylomicron remnants on endothelial cell function in the isolated perfused rat aorta. Atherosclerosis, 139 (2)(2) AbstractA system for the perfusion of the isolated rat aorta which allowed the study of both the uptake of chylomicron remnants by the artery wall and their effects on endothelial function was developed. Perfusion for 2 h with 125 I-labelled native or oxidised (by treatment with copper sulphate) chylomicron remnants showed that small amounts became associated with the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 37 publications
7
49
1
Order By: Relevance
“…Acutely impaired endothelium-dependent vasodilation after a high-fat meal has been found to be associated with postprandial hypertriglyceridemia. 2,13,14 Furthermore, postprandial hypertriglyceridemia may induce endothelial dysfunction through the direct effects of triglyceride-rich lipoproteins 3,4 and increasing oxidative stress in circulation. 1,15,16 These data indicate that lowering postprandial triglyceride concentration may lead to improvement of endothelial function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acutely impaired endothelium-dependent vasodilation after a high-fat meal has been found to be associated with postprandial hypertriglyceridemia. 2,13,14 Furthermore, postprandial hypertriglyceridemia may induce endothelial dysfunction through the direct effects of triglyceride-rich lipoproteins 3,4 and increasing oxidative stress in circulation. 1,15,16 These data indicate that lowering postprandial triglyceride concentration may lead to improvement of endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Moreover, postprandial triglyceride-rich lipoproteins and remnants directly impair endothelium-dependent vasodilation in animal models. 3,4 In addition, treatment strategies for lowering postprandial hypertriglyceridemia may lead to a reduction in CHD risk. 5 Inflammation is closely associated with endothelial dysfunction and atherosclerosis.…”
mentioning
confidence: 99%
“…As mentioned earlier, in a previous study we found chylomicron remnants to potentiate contraction to phenylephrine in an Ž . endothelium-dependent manner Grieve et al, 1997a . This effect was further potentiated when nitric oxide release was completely blocked by N v -nitro-L-arginine which rules out any possible effect on basal nitric oxide production.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary endpoints were glucose metabolism markers, inflammatory markers, and the serum adiponectin level. For the lipid metabolism Postprandial hyperglycaemia and hypertriglyceridaemia are also recognized as the risk for cardiovascular events related to postprandial endothelial dysfunction, in addition to classical risk factors [6][7][8][9][10] . Lipoprotein particles undergo partial hydrolysis predominantly through the action of lipoprotein lipase (LPL), forming smaller and denser particles known as remnants that are believed to be more atherogenic than larger triglyceride-rich lipoproteins (TRL).…”
Section: Measurement Of Serum Samplesmentioning
confidence: 99%